Pulmonary stenting for the treatment of sarcoid induced pulmonary vascular stenosis. - Condado, Jose F; Babaliaros, Vasilis; Henry, Travis S; Kaebnick, Brian; Kim, Dennis; Staton Jr, Gerald W (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: The best treatment of patients with external pulmonary vascular compression due to advanced sarcoidosis is unknown. Objectives: To report a single-center experience of percutaneous treatment for pulmonary vascular stenosis caused by external compression due to advanced sarcoidosis. Methods: We report a case series of 5 patients with biopsy confirmed advanced sarcoidosis, seen at our academic institution with worsening dyspnea despite increase of immunosuppressive therapy. All patients were evaluated by a multidisciplinary team (cardiology, pulmonary and radiology) using a multi-modality approach, including chest-computed tomography angiography, ventilation/perfusion scintigraphy, pulmonary function test, 6-minute walk test and heart catheterization. Results: Three out of five patients underwent pulmonary artery or vein angioplasty and stenting resulting in symptomatic improvement: Patient 1 had persistent symptomatic improvement measured by subjective and objective methods at 30 months; patient 2 required re-intervention due to recurrent pulmonary vein stenosis at 6-months followed by persistent improvement; and patient 3, had a procedure complicated with in-stent thrombosis requiring thrombolysis and anticoagulation with improvement. The remaining two patients were medically treated because underlying thromboembolic disease (patient 4) and diffuse pulmonary vein stenosis not amenable to percutaneous intervention (patient 5). Conclusions: Pulmonary vascular stenosis from external compression can be a rare but unrecognized caused of worsening symptoms in advanced sarcoidosis. Pulmonary vascular angioplasty and stenting can provide clinical benefit in select patients.